2014
DOI: 10.1111/pcn.12240
|View full text |Cite
|
Sign up to set email alerts
|

Association of autism tendency and hemodynamic changes in the prefrontal cortex during facial expression stimuli measured by multi‐channel near‐infrared spectroscopy

Abstract: Aim:The aim of this study is to examine the hemodynamic changes induced by the cognitive process of facial expression by using multi-channel nearinfrared spectroscopy in healthy subjects with varying degrees of autism tendency.Methods: Subjects were 38 volunteers, 20 men and 18 women. Autism tendency was measured by the Autism Spectrum Quotient. The hemodynamic changes in the prefrontal cortex were measured by 24-channel near-infrared spectroscopy system, while subjects were asked to judge their own emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
3
18
0
Order By: Relevance
“…This is in line with a functional magnetic resonance imaging (fMRI) study showing that higher AQ scores were associated with decreased white matter volume and deactivation of the STS (Von dem Hagen et al., ). In a more direct comparison of a clinical and nonclinical group, Hosokawa, Nakadoi, Watanabe, Sumitani, and Ohmori () applied a research paradigm to TD individuals that had previously been used on individuals with ASD. Their results showed that the degree of autistic traits people exhibited negatively correlated with the hemodynamic change the PFC showed in response to negative facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with a functional magnetic resonance imaging (fMRI) study showing that higher AQ scores were associated with decreased white matter volume and deactivation of the STS (Von dem Hagen et al., ). In a more direct comparison of a clinical and nonclinical group, Hosokawa, Nakadoi, Watanabe, Sumitani, and Ohmori () applied a research paradigm to TD individuals that had previously been used on individuals with ASD. Their results showed that the degree of autistic traits people exhibited negatively correlated with the hemodynamic change the PFC showed in response to negative facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…The expression recognition task was developed by referencing the facial expressions that Hosokawa et al used eight facial expressions (anger, sadness, happiness, contempt, disgust, surprise, fear and neutral) [22]. Static images of Japanese models were selected from the ATR (ATR International Human Information Science Laboratories) face database containing eight facial expressions [28].…”
Section: Expression Recognition Taskmentioning
confidence: 99%
“…On the other hand, Hosokawa et al examined the relationship between autistic tendencies and the frontal cortex blood mobilization in expression recognition tasks in healthy people [22]. Results showed that when a healthy person exhibited thoughts and behavioral patterns characteristic of ASD, it was difficult for them to recognize expressions, and they had decreased prefrontal cortex activity.…”
Section: Introductionmentioning
confidence: 99%
“…The high autism-trait group had poorer performance when recognising anger, disgust and sadness, as shown by more errors and a higher intensity needed to identify the emotions, compared to the low autismtrait group. Similarly, Hosokawa, Nakadoi, Watanabe, Sumitani and Ohmori (2015) found that higher AQ scores were negatively correlated with the ability to identify fearful facial expressions.…”
Section: The Broader Autism Phenotypementioning
confidence: 88%
“…Several studies have demonstrated associations between non-clinical autism-like traits and differences in emotion processing. Participants with higher levels of autism-like traits show less spontaneous imitation of facial expressions, and poorer recognition of negative facial expressions, compared to those with lower levels of autism-like traits (Hermans et al, 2009;Hosokawa et al, 2015;Poljac, Poljac & Wagemans, 2012). Additionally, those with higher levels of autism-like traits show poorer understanding of general social non-verbal behaviours and poorer recognition of facial emotion, compared to those with lower levels of autism-like traits (Ingersoll, 2010).…”
Section: Introductionmentioning
confidence: 92%